Uwagi na marginesie edycji bazyliańskiego poematu O zabiciu Młodzianków - Rusnak, Radosław (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This paper is intended to gather some remarks regarding a first published late-Baroque poem TheMassacre of the Innocents, being an anonymous Polish translation of Giambattista Marino’ s work. Aftergiving a sketchy characterization of the poem and displaying the main reasons of its publication, the authorproceeds to conclusions drawn from the simultaneous reading of three existing versions of the Polishtext survived in one of the Ossolineum manuscripts. He dwells on the paths the translator takes arduouslyforming and transforming his version of the Italian poem, pointing out the main types of corrections hemakes and trying to present a reasonable explanation for his artistic choices. The paper intends though toshape a more profound picture of the work taking into account not only the final (or the one consideredto be such) form of the text but also all the traces of the translator’ s continuous labour conserved in theextant versions of the Polish poem.